Early Lymphocyte Loss and Increased Granulocyte/Lymphocyte Ratio Predict Systemic Spread of Streptococcus pyogenes in a Mouse Model of Acute Skin Infection - Loof, Torsten G.; Sohail, Aaqib; Bahgat, Mahmoud M.; Tallam, Aravind; Arshad, Haroon; Akmatov, Manas K.; Pils, Marina C.; Heise, Ulrike; Beineke, Andreas; Pessler, Frank (Frontiers in Cellular and Infection Microbiology, 2018)
Background. Group A streptococci may induce lymphopenia, but the value of lymphocyte loss as early biomarkers for systemic spread and severe infection has not been examined systematically. Methods. We evaluated peripheral blood cell indices as biomarkers for severity and spread of infection in a mouse model of Streptococcus pyogenes skin infection, using two isolates of greatly differing virulence. Internal organs were examined histologically. Results. After subcutaneous inoculation, strain AP1 disseminated rapidly to peripheral blood and internal organs, causing frank sepsis. In contrast, seeding of internal organs by 5448 was mild, this strain could not be isolated from blood, and infection remained mostly localized to skin. Histopathologic examination of liver revealed microvesicular fatty change (steatosis) in AP1 infection, and examination of spleen revealed elevated apoptosis and blurring of the white pulp/red pulp border late (40 h post infection) in AP1 infection. Both strains caused profound lymphopenia, but lymphocyte loss was more rapid early in AP1 infection, and lymphocyte count at 6 h post infection was the most accurate early marker for AP1 infection (area under the receiver operator curve [AUC] = 0.93), followed by the granulocyte/lymphocyte ratio (AUC=0.89). Conclusions. The results suggest that virulence of S. pyogenes correlates with the degree of early lymphopenia and underscore the value of peripheral blood indices to predict severity of bacterial infections in mice. Early lymphopenia and elevated granulocyte/lymphocyte ratio merit further investigation as biomarkers for systemic spread of S. pyogenes skin infections in humans and, possibly, related pyogenic streptococci in humans and animals.